METASTASIS OTAK TIPE MILIER PADA KASUS ADENOKARSINOMA PARU DENGAN MUTASI EGFR T790M - I Made Oka Adnyana*, Ni Luh Putu Eka Arisanti** (NEURONA, 2020)
METASTASIS IS THE MOST COMMON INTRACRANIAL TUMOR WITH THE NUMBER OF EVENTS EXCEEDING PRIMARY BRAIN TUMORS IT STILL HOLDS HIGH MORTALITY AND MORBIDITY RATE TO DATE MOST OF THE METASTASES ARE MACROSCOPIC PARENCHYMAL MASS LESIONS WITH SURROUNDING EDEMA AND OCCURRED IN THE GRAYWHITE MATTER JUNCTION MILIARY BRAIN METASTASIS IS A RARE CONDITION WITH GENERALLY POOR PROGNOSIS